2019
DOI: 10.3988/jcn.2019.15.2.184
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 12 Chinese Patients with Proline-to-Leucine Mutation at Codon 102-Associated Gerstmann-Sträussler-Scheinker Disease

Abstract: Background and Purpose Gerstmann-Sträussler-Scheinker disease (GSS) with a proline-to-leucine mutation at codon 102 (P102L) in the PRNP gene is the most frequently reported GSS subtype worldwide. This study aimed to determine the epidemiological, clinical, genetic, and laboratory characteristics of 12 Chinese patients with P102L-associated GSS (henceforth P102L GSS). Methods The enrolled P102L GSS cases were analyzed according to the diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
(47 reference statements)
0
8
0
1
Order By: Relevance
“…[9][10][11] Long-term survivors have been reported to have either sCJD or vCJD. 9,[12][13][14] The aims of this prospective study are (1) to report all forms of human prion diseases identified in Taiwan; (2) to calculate the temporal trends in incidence by gender and age; and (3) to assess the mortality rate and disease duration.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Long-term survivors have been reported to have either sCJD or vCJD. 9,[12][13][14] The aims of this prospective study are (1) to report all forms of human prion diseases identified in Taiwan; (2) to calculate the temporal trends in incidence by gender and age; and (3) to assess the mortality rate and disease duration.…”
Section: Introductionmentioning
confidence: 99%
“…The survival time for PRNP P102L variant patients has varied among several reports ( Table 2 ). The median survival times in previous studies were as follows: China (12 cases), 6 months 16 ; Czech Republic (7 cases), 28 months 9 ; Germany (9 cases), 68 months 14 ; and Ariake PRNP P102L variant, 63 months. The disease duration did not differ significantly between the Ariake PRNP P102L variant and German cases (65±23 vs. 65±26 months).…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, the disease duration was shorter for female patients and those who were younger at onset in Chinese cases. 16 Further research is needed to clarify the mechanisms underlying the differences in these tendencies between geographical areas.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical phenotype of GSS can be quite variable and although DWI imaging is typically negative in GSS, rare cases report a positive MRI. 6 DWI imaging associated with the PRNP-G131V/129M variant was not reported, leaving that question open. Thus, the question of whether the PRNP-G131R/ 129V variant predisposes PrP to misfold into a CJD-determining conformation rather than the GSS conformation induced by PRNP-G131V/129M will remain unanswered until the availability of direct histologic evidence.…”
Section: Discussionmentioning
confidence: 99%